Lesch Alcoholism typology – clinical picture - Iwanicka, Katarzyna; Malicki, Dariusz; Olajossy, Marcin (Current Problems of Psychiatry, 2011)
The article presents alcoholism typology created by Otto Lesch. The discussed typology was based on longitudinal studies among patients. The analyzed data concerned different reasons for consuming alcohol, patients’ personality structure, as well as neuro-physiological parameters of their functioning. The first type, called “the allergy model”, is connected with severe withdrawal symptoms, such as tremor, tachycardia or anxiety. In this case, alcohol is used to cope with withdrawal symptoms. Type II, named “the fear model”, regards patients with primal anxiety and mood disorder. In this type alcohol is consumed in order to alleviate tension and anxiety. Patients included in the type III, use alcohol as antidepressant that enhances mood and reduces associated symptoms of psychiatric disorders. The last one, type IV, called “the conditioning model”, refers to patients, who underwent a central nervous system trauma in the early childhood. Moreover, these patients experience impaired cognitive functioning and present less criticism towards effects of overusing alcohol.